Olympic Dreams The Impact of Mega-Events on Local Politics - Burbank, Matthew J. (Explorations in Public Policy, 2022)
What drives cities to pursue large-scale, high-profile events like the Olympic games? What are the consequences for citizens and local governments? Investigating local politics in three U.S. cities-Los Angeles, Atlanta, and Salt Lake City-as they vied for the role of Olympic host, this book provides a compelling narrative of the evolving political economy of modern megaevents. The authors reveal how the megaevent strategy typically is initiated by a coalition of public and private elites; how citizen involvement is managed and often curtailed; and how latent development agendas are revived and refocused to leverage Olympic opportunities. In assessing the impact of megaevent-driven growth, they look beyond the tax revenues and stadium costs to offer a nuanced examination of the ways Olympic dreams affect local governance and social conditions in urban economies